(untitled) (Jurnal Bahasa, 2001)
The language of Sejarah Melayu is one of high literature, i.e. a beautiful language written by weaving existing linguistic elements in a harmonious flow of rhythm which at the same time gives rise to a picture that is most vivid to the perception of the reader. This characteristic rests with the mastery of the author in utilizing his creativity in presenting his story so that it comes out in an integrated whole, and incorporated into it his own ideas about things. From the language and the discourse of Sejarah Melayu, one can conclude that its author belonged to the palace community, and could understand religious books written in Arabic. Furthermore, he was an intellectual of his age, and one who had a sense of humour.